The ‘how’ for sustainability: Answering market pressure through green strategy and green production - Johan, Ahmad; Rahayu, Agus; Wibowo, Lili Adi; Yuliawati, Ayu Khrisna (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This study aims to examine the influence of market pressure on green strategy and green production while also looking at its impact on MSMEs' sustainability. The authors also investigate the indirect influence of market pressure on green production through the mediating role of green strategy.Design/Methodology/Approach: This study was carried out on batik craft, fashion, and convection MSMEs oriented to the green concept in West Java Province, with a number of samples of 185 MSMEs. The data obtained were then analyzed using the structural equation modeling technique with SmartPLS software.Research findings: The results of this study demonstrated the positive influence of market pressure on green strategy and green production, and both influenced MSMEs' sustainability. Furthermore, green strategy has been proven to have a positive influence on green production and could mediate the influence of market pressure on green production.Theoretical Contribution/Originality: This study contributes to the literature by widening the antecedent of green strategy, green production, and MSMEs sustainability from the external side, namely market pressure, which is rarely elaborated.Practitioners/Policy Implications: Managers and owners of batik craft, fashion, and convection MSMEs must prepare themselves to answer the calls for sustainability that come from their stakeholders, such as the market and government. Green strategy and green production must be incorporated into their business to achieve sustainability.Research Limitations/Implications: This study has not yet considered the existence of moderating variables, such as firm size, government regulation, or organizational competitiveness. These additional variables can be a sign for firms to understand when the time is to implement their strategy to achieve sustainability according to the underlying conditions of the moderators.